Analysis of Factors That Influence the Performance of Population and Civil Registration Service Employees of Aru Islands Regency - Sulfaidah, Sulfaidah; Oktarina, Harti (Universitas Negeri Makassar, 2024)
This research aims to determine (1) the partial influence of Leadership Style, Discipline, Motivation and Education on the Performance of Population and Civil Registration Service Employees in Aru Islands Regency and (2) the influence of Leadership Style, Discipline, Motivation and Education simultaneously on Employee Performance. Population and Civil Registration Service in Aru Islands Regency. The sampling technique uses a saturated sampling technique by using the entire population as the sample. The data collection technique is by using a questionnaire distributed directly by the researcher. The results of the research show that Leadership Style, Discipline, Motivation and Education have a partial or simultaneous influence on the Performance of Population and Civil Registration Service Employees in Aru Islands Regency as seen from the sig value. < alpha value (0.05). The performance variable that can be explained by the leadership style, motivation and work discipline variables is 97.4%. Meanwhile, the remaining 0.026 or 2.6% variables were not examined by the author, such as organizational culture, leadership, etc.